ANALISIS KOMUNIKASI KELUARGA ANTARA PERANTAU DENGAN ORANG TUA (STUDI PADA PERANTAU SUMATERA SELATAN DI KOTA BATAM) - Milta, Dea; Abidin, Sholihul (SCIENTIA JOURNAL, 2023)
Family communication between migrants (children) and their parents is a verbal and non-verbal interaction that occurs between children who live far away from home and theirparents. This communication allows them to stay connected, share information, andmaintain emotional relationships despite the distance. This research employed a qualitativemethod, utilizing Mery Anne Fitzpatrick's family relationship schema theory. The theoryillustrates communication practices within a family involving the roles of parents and children.The research findings indicate that the forms and patterns of communication adopted bymigrants from South Sumatra residing in Batam City are verbal, aligned with thecommunication practices between children and parents within Fitzpatrick's concept. Throughinterviews as one of the data collection techniques, researchers discovered howcommunication occurs using various media such as WhatsApp and video calls, enablingmigrants to exchange information with their parents in their hometown. In conclusion, thisstudy demonstrates the significance of family communication between migrants from SouthSumatra in Batam City and their parents in the hometown to overcome the obstacle ofdistance. Effective communication and strong emotional bonds help address this challenge.The family relationship schema theory provides valuable insights into understanding familycommunication, particularly between migrant children and their parents, which is crucial inmaintaining family ties despite the distance and physical separation